Carpal tunnel syndrome: clinical features, diagnosis, and management. Issue 12 (November 2016) - Padua, Luca; Coraci, Daniele; Erra, Carmen; Pazzaglia, Costanza; Paolasso, Ilaria; Loreti, Claudia; Caliandro, Pietro; Hobson-Webb, Lisa D
Summary: Carpal tunnel syndrome is the most common peripheral nerve entrapment syndrome worldwide. The clinical symptoms and physical examination findings in patients with this syndrome are recognised widely and various treatments exist, including non-surgical and surgical options. Despite these advantages, there is a paucity of evidence about the best approaches for assessment of carpal tunnel syndrome and to guide treatment decisions. More objective methods for assessment, including electrodiagnostic testing and nerve imaging, provide additional information about the extent of axonal involvement and structural change, but their exact benefit to patients is unknown. Although the best means of integrating clinical, functional, and anatomical information for selecting treatment choices has not yet been identified, patients can be diagnosed quickly and respond well to treatment. The high prevalence of carpal tunnel syndrome, its effects on quality of life, and the cost that disease burden generates to health systems make it important to identify the research priorities that will be resolved in clinical trials.